Strategy Preparation at PT. Permata Salsabila Mulia Special Umrah and Hajj Travel Organizer Bureau - Suyitno, Suyitno; Wening, Nur (Jurnal Manajemen, 2025)
Permata Salsabila Mulia is a company specializing in the organization of Umrah and special Hajj pilgrimage travel. Increas-ing competition in this industry necessitates the development of effective business strategies to enhance competitiveness and en-sure sustainability. This study aims to formulate strategic recom-mendations for PT. Permata Salsabila Mulia in addressing market challenges, optimizing organizational potential, and meeting cus-tomer expectations. The research employs SWOT analysis and external business environment analysis to identify key strengths, weaknesses, opportunities, and threats. Based on the analysis results, strategic recommendations were developed, including strong branding development, improved marketing strategies, service diversification, service quality enhancement, strategic partnerships, and continuous innovation. These strategies are expected to increase the company's competitive advantage and strengthen its position in the Umrah and Hajj pilgrimage travel industry.